2003
DOI: 10.1148/rg.233025121
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cervical Spine: Normal Anatomy, Variants, and Trauma

Abstract: Emergency radiologic evaluation of the pediatric cervical spine can be challenging because of the confusing appearance of synchondroses, normal anatomic variants, and injuries that are unique to children. Cervical spine injuries in children are usually seen in the upper cervical region owing to the unique biomechanics and anatomy of the pediatric cervical spine. Knowledge of the normal embryologic development and anatomy of the cervical spine is important to avoid mistaking synchondroses for fractures in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(157 citation statements)
references
References 80 publications
2
148
0
7
Order By: Relevance
“…Skeletally immature children are at risk of misdiagnosis because of incomplete fusion of their ossifying C2 vertebra [7]. Development of C2 involves ossification of four separate ossification centers consisting of the vertebral body, the odontoid, and right and left facet/pars/lamina.…”
Section: Pediatric Fractures Of the Atlasmentioning
confidence: 99%
“…Skeletally immature children are at risk of misdiagnosis because of incomplete fusion of their ossifying C2 vertebra [7]. Development of C2 involves ossification of four separate ossification centers consisting of the vertebral body, the odontoid, and right and left facet/pars/lamina.…”
Section: Pediatric Fractures Of the Atlasmentioning
confidence: 99%
“…This finding might be of diagnostic importance since in children, the support of motion in the cervical spine is at the C2-C3 level, while in the adult cervical spine is at the C5-C6 level (Lustrin et al 2003). [12] Gender distribution of the cervical vertebral anomalies 2 (2.7%) males and 7(9.46%) females were found to have CVA. In the present study, more females were found to have cervical vertebral anomalies.…”
Section: Discussionmentioning
confidence: 87%
“…A secondary ossification center (os terminale) at the apex of the odontoid process appears between 3 and 6 years of age and usually fuses by 12 years. 16,17 The cruciate and alar ligaments share the common mesenchymal origin in the tip of the primitive odontoid process. 12,18 The apical ligament is a functional vestige of the notochord and arises from either the notochord or its sheath.…”
Section: Discussionmentioning
confidence: 99%